MEMPERKUAT KOMPETENSI ANALISIS SPASIAL BERBASIS QGIS UNTUK PEMETAAN LOKASI PENELITIAN - Sri Asmirani; Farida Islamiah; Muhammad Ashdaq; Rezki Nurfadillah; Syahrul Syahrul (Universitas Ichsan Sidenreng Rappang, 2026)
This community service activity aims to improve the competence of Digital Business students in utilizing QGIS as a spatial analysis tool in mapping research locations and location-based business decision making. The activity was carried out in the form of practice-based training (experiential learning) which included the delivery of basic concepts of Geographic Information Systems (GIS), introduction to QGIS, and spatial analysis practices using real data of culinary business locations in Makassar City. The implementation method included the stages of identifying needs, preparation, training implementation, spatial analysis practices (distribution mapping, density analysis, market gap identification, and strategic location determination), as well as evaluation through pre-test and post-test. The results of the activity showed a significant increase in participant competence. After participating in the training, the average post-test score increased to 82.50% which is in the good category. Overall, the assessment indicators of understanding the concept of basic use of QGIS, analysis and interpretation of maps overall increased by an average of 32.25% points indicating that the training had a significant positive impact on increasing participant competence in utilizing QGIS. These findings indicate that the use of QGIS not only improves conceptual understanding, but also applicative skills in spatial analysis. Thus, this training is effective in improving geospatial technology literacy and supporting data-driven business decision-making. The implementation of spatial analysis through QGIS is expected to be an alternative approach to mapping research locations and developing spatial information-based entrepreneurship.